Intra‐Island Coulomb Correlations in PEDOT:PSS Thin Films; Saturation of Spin Polarization Magnetoresistance. (15th March 2021) - Nikiforov, Daniel; Tessler, Nir; Ehrenfreund, Eitan
Abstract: Magnetic field and temperature dependence of the magneto‐conductance (MC) of thin films made of self‐p‐doped poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) having room temperature conductivity of ≈200 S cm −1 in the range of fields B = 0–14 T and temperatures T = 1.8–300 K are reported. At B = 0 and for current parallel to the film surface, the conductance follows a variable range hopping mechanism in two dimensions. It is shown that the finite Coulomb correlations, U, within the nano‐crystalline PEDOT islands dominates MC at low temperatures and high fields. At T = 1.8 K, the intra‐island Coulomb correlation spin polarization mechanism is already saturated for B > 10 T establishing a finite minimum of ≈2 meV for U . This small value of U is in line with the delocalized nature of the holes within the PEDOT islands and the relatively high conductivity that makes it essential in organic opto‐electronics. Abstract : Magnetoconductance of poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) thin films in the variable range hopping regime is dominated by the Coulomb correlation energy U within the nano‐crystalline positively charged PEDOT islands at low temperatures and high magnetic fields. Lower limit U ≥ 2 meV is determined from the saturation of spin polarization at T = 1.8 K and B ≈10 T.